Perception on the Use of Artificial Intelligence for Curbing Examination Malpractices during Standardised Examinations in Nigeria - OLADELE, Jumoke Iyabode; JOSEPH, Grace; ISSA, Jamiu (Ilorin Journal of Education, 2024)
This study examined the level of perception of the use of Artificial Intelligence for curbing examination malpractice in Nigeria. Three research questions were formulated to guide the study. The study adopted qualitative research of the exploratory type. The population of this study comprised of twelve examination body staffs from JAMB, NECO, WAEC and NABTEB Ilorin. Kwara State. The research instrument used for this study was a designed interview guide titled “Artificial Intelligence in Curbing Examination Malpractice during Standardized Examinations”. The research questions were answered using a thematic approach. Findings from this study revealed that JAMB makes use of proctoring software while NECO, WAEC and NABTEB makes use of human proctors. More so, findings show that staffs from all the examination bodies have positive thoughts towards the use of Artificial Intelligence in curbing examination malpractice. Moreover, Artificial Intelligence significantly contributes to curbing examination malpractice. It is hereby recommended among others that AI proctoring software should be adopted in curbing examination malpractice supported with human proctors at the initiation stages.